IMPLEMENTASI MODEL BISNIS CANVAS PADA USAHA BUBUR ORGANIK STUDI KASUS PT. ROFINDIYA EKAMULIA SUKSES - Lidia, Lidia; Triyono, Triyono (Prodi Manajemen Bisnis Syariah, 2024)
This study aims to find out how to apply the Business Model Canvas with the current Business Business Model Canvas and Future Business Model Canvas organic porridge PT. Rofindiya Ekamulia Sukses. The problem in this study is that the